RELATIONSHIP BETWEEN DISPOSITIONAL MINDFULNESS AND LIFE SATISFACTION AMONG UNDERGRADUATE STUDENTS IN MALAYSIA: COGNITIVE REAPPRAISAL AS THE MEDIATOR (Jurnal Kemanusiaan, 2023)
Undergraduate students are facing different challenges and stressors in their life, which may lower their life satisfaction. Dispositional mindfulness has been found to increase life satisfaction, and this relationship might include cognitive process namely cognitive reappraisal. Hence, grounded in Mindfulness-to-Meaning Theory, this study examined cognitive reappraisal as the mediator in the relationship between dispositional mindfulness and life satisfaction among 147 undergraduate students (aged 18-25 years old) who were studying in Malaysia. A non-experimental correlational design was used, where the students were required to fill in three questionnaires through Google Form survey, the results were analysed through hierarchical multiple regression. The results supported all four hypotheses, with significant positive relationships found among dispositional mindfulness, cognitive reappraisal and life satisfaction. Cognitive reappraisal partially mediated the relationship between dispositional mindfulness and life satisfaction. The findings provide valuable information for the experts to devise mindfulness interventions by incorporating cognitive reappraisal strategies, allowing students to use cognitive reappraisal to cope with challenges, improving life satisfaction.